Clinical observation on the efficacy of Tongdu Tuina manipulation in the treatment of primary enuresis in children - Jie Li-Pu (Open Medicine, 2023)
The objective was to explore the efficacy of Tongdu Tuina manipulation in the treatment of primary single-symptom enuresis in children. A total of 102 children aged 5–16 with primary single-symptom enuresis were included in this study and randomly assigned to the Tuina group, the medication group and the control group, with 34 children in each group. The Tongdu Tuina group included manipulation of the Guanyuan, Qihai, Zhongji, Mingmen, kidney, Baihui, Sishencong and bladder acupoints, five times a week, the medication group was treated with 0.1 mg desmopressin acetate every night, and in the control group, the patients were given foods with high water content and underwent water deprivation 2 h before bedtime every night. The intervention time of each group was 1 month. The participants were followed up on Day 1 following treatment, as well as half a month, 1 month and 3 months after the implementation of the intervention measures, and the effective rate, the incidence of enuresis per week and the recurrence rate were calculated. As a result baseline demographic characteristics were comparable among 102 patients. Overall, 32 patients in the Tongdu Tuina group, 30 patients in the medication group and 34 patients in the control group completed the intervention. After half a month of treatment, there was no significant difference in the therapeutic efficacy among the three groups (P = 0.158), but each treatment could effectively reduce the frequency of weekly enuresis. The frequency of weekly enuresis in the Tongdu Tuina group was 3.8 ± 1.1 times, while that in the medication group was 4.0 ± 2.0 times. The frequency of weekly enuresis in the control group was 4.7 ± 1.8 times, and the difference was statistically significant (P = 0.016). After 1 month of treatment, the effective rates of the Tongdu Tuina group and the medication group were significantly increased (87.5% vs 83.33%, P < 0.0001), which was not the case with the control group. The frequency of enuresis was 1.9 ± 2.1 times per week in the Tongdu Tuina group, 2.4 ± 1.8 times per week in the medication group and 4.0 ± 0.9 times per week in the control group after 1 month of treatment. The difference between the three groups was statistically significant (P = 0.021), and there was a difference between the Tongdu Tuina group and the medication group (P < 0.0001). There was no significant difference between recurrence rate and the incidence of adverse events (P = 0.837, P = 0.856). In conclusion, both Tuina manipulation and desmopressin treatment can effectively improve children’s primary single-symptom enuresis with safety. However, Tongdu Tuina therapy may be superior to desmopressin treatment.